Teaching English to young learners critical issues in language teaching with 3-12 year olds - Bland, Janice (London, England Bloomsbury Academic, 2015)
Aimed at student teachers, educators and practitioners, Teaching English Language to Young Learners outlines and explains the crucial issues, themes and scenarios relating to this area of teaching. Each chapter by a leading international scholar offers a thorough introduction to a central theme of English as a foreign language (EFL) with preteens, with clear presentation of the theoretical background and detailed references for further reading, providing access to the most recent scholarship
Includes bibliographical references and index.
Keywords: English language -- Study and teaching (Elementary) -- Foreign speakers; Second language acquisition; Educational tests and measurements; Language and education